Scientific Approaches In Al-Biruni’s Kitab Al-Hind: A Pre-Modern Framework For Comparative Religion - Nematullo Mukhamedov; Nurulloh Turambetov (Academia One Publishing, 2025)
This article examines the pioneering methodologies employed by Abu Rayḥan al-Biruni in his comparative study of religions, with particular emphasis on his work Kitāb al-Hind. It explores how Al-Biruni’s scientific approach – based on empirical observation, philological precision, and cultural empathy–set a precedent for future developments in religious studies. By analyzing his techniques within both historical and contemporary frameworks, the article argues for AlBiruni’s continued relevance in academic discourse. The study also evaluates his contributions to interreligious understanding and proposes directions for future research on non-Western foundations of comparative religion
Keywords: Al-Biruni; comparative religion; scientific methodology